Informal Learning Projects as a Vehicle for Collaborative Professional Development in Online Communities - Bowskill, Nicholas (Proceedings of the International Conference on Networked Learning, 2004)
This article is a theoretical study looking at a new role for online learning communities. This role is to provide support from members for others to bring informal learning projects to be collaboratively developed and explored in a meaningful dialogue. This model creates a symbiotic relationship that is flexible and authentic within the context of global education. In this article the author reviews the experience of taking an informal learning project to an online community for collaborative support. The particular project under review sought to develop a support framework within an online community for other members’ projects. An implemented model is described and considered within the framework of community capacity. To support learning at all levels, a method is described for developing exploring community history and identity through the sharing of narratives and the construction of a Library of Experience. This article seeks to explore the potential of online communities to support and develop new practices around collaborative mentoring and informal learning projects. This study seeks to address the following research hypotheses: Informal learning can be utilised as a developmental approach in an online open environment Online communities can learn from involvement with informal learning projects and they can support the development of a community history and identity Online communities can be effective in supporting informal learning projects In this article, I describe an initiative arising in part from earlier work (Bowskill et al, 2001) that seeded the development of a model of support and development within an online community. This model is my own informal learning project (Tough, 1971) and forms part of the author’s doctoral research at the University of Sheffield. This model is innovative in the way it provides an open member-to-member service that is culturally sensitive and inclusive. Jobring (2002) is interesting in describing online learning communities as context providers and a move away from being content providers. Jobring (2002) also notes 3 key areas of concern which are community management, community measurement and skills for working within communities. Community measurement asks how we might come to know what is being learned within a community. This is important and in this paper I offer a clear framework to facilitate a view of what is being learned through the adoption and support of informal learning projects and the creation of archived case studies from within the community. This in turn provides a method for management in a voluntary setting. The point raised about skills is also interesting as Jobring (2002) identifies 7 skills marking an apprenticeship from initial joining through to a position of greater autonomy. In the initiative described below, I mark out a similar apprenticeship structure around involvement in co-mentoring of informal learning projects. This apprenticeship is a clearer more practical route to developing autonomy within an engaged and focussed collaborative context.